Robust transmission using channel encoding towards 5G New Radio: A telemetry approach. (October 2021) - Sharma, Vipin; Arya, Rajeev; Kumar, Sandeep
Highlights: We developed a robust channel transmission under adaptive modulation and coding for a massive machine type communication device in 5G new radio In first time, a mode-selection and distance statistics algorithm are simultaneously evaluated and achieved an efficient modulation along with robust transmission. Mode-selection algorithm is employed to predict the environmental condition while distance statistics provides the feedback mechanism of transmission channel condition. The simulation analysis of BER performance verified the optimum threshold for channel estimation. Abstract: This paper presents a robust channel encoding scheme under adaptive modulation and coding for a massive machine type communication device in 5G new radio. For the very first time, mode-selection and distance statistics algorithms have been simultaneously evaluated, in which together it provides the closest approximation of efficient adaptive modulation and coding with robust transmission. The prediction of optimum adaptive modulation and coding is based on the analysis of uplink packet using distance statistics, and downlink packet using mode-selection mechanism. The performance of 5G new radio by incorporating OFDM subcarrier has been evaluated using analytical as well as simulation approach. Mode-selection algorithm has been considered to predict the environmental condition under a fading channel while the distance statistics provide feedback of the previously transmitted channel condition. The result of both the approaches provide a better bit error rate for adaptive modulation & coding profile under 1/4, 1/18, 1/16 and 1/32 cyclic prefix. Graphical abstract: Developed a robust telemetry approach under adaptive modulation and coding scheme for a massive machine type communication device in 5G new radio. The mode-selection and distance statistics are simultaneously employed and evaluate to analyze an uplink and downlink packets under different prefix cycles and finally achieves a better bit error rate performance. Image, graphical abstract